Postpartum Hemorrhage Following Vaginal and Cesarean Section Deliveries at a Single Tertiary Hospital: A Five-year Cross-sectional Study - Miriam George Fenn; Maisa Al Falahi; Taif Al Hannai; Lubna Al Shukaili; Nihal Al Riyami (Oman Medical Journal)
Objectives: This study aimed to examine the prevalence, etiology, management, and outcomes of postpartum hemorrhage (PPH) following vaginal and cesarean delivery. Methods: We conducted a cross-sectional study on women who delivered at Sultan Qaboos University Hospital from January 2017 to December 2021 and experienced PPH. PPH was defined as per World Health Organization criteria of blood loss > 500 mL after vaginal delivery and 1000 mL after cesarean delivery. The study evaluated demographic parameters, pre-delivery and discharge hemoglobin, estimated blood loss, etiology, pharmacological, mechanical, and surgical interventions for PPH, and the need for blood products. Results: There were 18 136 vaginal deliveries, of which 729 women had PPH, with a prevalence of 4.0%. Among 2771 cesarean sections, 360 women had PPH, with a prevalence of 13.0%. Hemoglobin < 11 g/dL was found in 278 (38.1%) and 140 (38.9%) women before vaginal delivery and cesarean section, respectively. Grand multiparas had the highest prevalence of PPH after vaginal delivery (42.7%). In cesarean deliveries, the majority (48.6%) were women with parity 2–4. Poor uterine tone was the cause of PPH in 616 (84.5%) vaginal deliveries and 263 (73.1%) cesarean deliveries. Surgical interventions were required in 244 (33.5%) women after vaginal delivery and 82 (22.8%) women after cesarean section. The average blood loss was 860 mL after vaginal delivery and 1400 mL after cesarean section. Blood transfusion was required in 74 (10.2%) women after vaginal delivery and 127 (35.3%) women after cesarean section. There was one maternal mortality due to atonic PPH after vaginal delivery. Conclusions: Active management of the third stage of labor and repeated emergency obstetric drills have reduced adverse outcomes. Addressing anemia in pregnancy and further research on carbetocin use in cesarean sections are recommended.